Analysis of Factors Influencing the Development of Xerostomia during Intensity-Modulated Radiotherapy - Randall, Ken (2013)
OBJECTIVES: Factors influencing xerostomia during intensity-modulated radiation therapy (IMRT) were assessed. METHODS: A 6-week study of 32 head and neck cancer (HNC) patients was performed. Subjects completed the Xerostomia Inventory (XI) and provided stimulated saliva (SS) at baseline, week two and at end of IMRT. Influence of SS flow rate (SSFR), calcium and mucin 5b (MUC5b) concentrations and radiation dose on xerostomia was determined. RESULTS: HNC subjects experienced mean SSFR decline of 36% by visit two (N=27; p=0.012) and 57% by visit three (N=20; p=0.0004), Concentrations of calcium and MUC5b increased, but not significantly during IMRT (p>0.05). Xerostomia correlated most with decreasing salivary flow rate as determined by Spearman correlations (p<0.04) and linear mixed models (p<0.0001). CONCLUSIONS: Although IMRT is sparing to the parotid glands, it has an early effect on SSFR and the constituents in saliva in a manner that is associated with the perception of xerostomia.